Intervensi Strategis Peningkatan Ketahanan Pangan Pedesaan Propinsi Jawa Tengah (Strategic Intervention in Promoting Village-Level Food Security in Central Java) - Mochammad Maksum (agriTECH, 2006)
The emergence of the food deficient phenomena in many localities proved that aggregative progress in food security does not necessarily guarantee the attainment of local food security in every village of the country. Anticipating that fact, therefore, this research was conducted to identify possible intervention strategies for intervening local social capacity in self-strengthening local food security system at village level based on selected typological character of village samples in Central Java. Four poor villages representing village typology were selected purposively to represent both the food-exporting and food-importing areas. Based on human right based approach, this comparative research found out a set of significantly different strategies in developing local capacity in food security through both demand and supply management. Supply capacity of exporting village must be strengthened through effective supply and storage system, whereas demand-based importing village capacity must be strengthened through income protection and management to improve purchasing power in meeting daily need for imported food. In addition, local empowerment centralized on institutional capacity building is hereby recommended for both the food exporting and importing villages to enable local institution to be skillful in resource mapping, effective in advocating people participation, and powerfill in facilitating participative decision making.